Clinical Outcomes Related to Protein Delivery in a Critically Ill Population: A Multicenter, Multinational Observation Study. (January 2016) - Nicolo, Michele; Heyland, Daren K.; Chittams, Jesse; Sammarco, Therese; Compher, Charlene
Objective: Optimal intake of energy and protein is associated with improved outcomes, although outcomes relative to protein intake are very limited. Our purpose was to evaluate the impact of prescribed protein delivery on mortality and time to discharge alive (TDA) using data from the International Nutrition Survey 2013. We hypothesized that greater protein delivery would be associated with lower mortality and shorter TDA. Methods : The sample included patients in the intensive care unit (ICU) ≥4 days (n = 2828) and a subsample in the ICU ≥12 days (n = 1584). Models were adjusted for evaluable nutrition days, age, body mass index, sex, admission type, acuity scores, and geographic region. Percentages of prescribed protein and energy intake were compared with mortality outcomes using logistic regression and with Cox proportional hazards for TDA. Results : Mean intake for the 4-day sample was protein 51 g (60.5% of prescribed) and 1100 kcal (64.1% of prescribed); for the 12-day sample, mean intake was protein 57 g (66.7% of prescribed) and 1200 kcal (70.7% of prescribed). Achieving ≥80% of prescribed protein intake was associated with reduced mortality (4-day sample: odds ratio [OR], 0.68; 95% confidence interval [CI], 0.50–0.91; 12-day sample: OR, 0.60; 95% CI, 0.39–0.93), but ≥80% of prescribed energy intake was not. TDA was shorter with ≥80% prescribed protein (hazard ratio [HR], 1.25; 95% CI, 1.04–1.49) in the 12-day sample but longer with ≥80% prescribed energy in the 4-day sample (HR, 0.82; 95% CI, 0.69–0.96). Conclusion : Achieving at least 80% of prescribed protein intake may be important to survival and shorter TDA in ICU patients. Efforts to achieve prescribed protein intake should be maximized.